Leitura: inferências e contexto sócio-cultural - Regina Lucia Peret Dell'isola (1988)
In this work, a searching study is presented in which reading from only one text are analysed comparing a drawing of inferences between representative individuals from distinct social classes. It has by aim to verify if there is influence from the social and cultural factor in the generation of inferences, which results in different readings from individuals. It is widely known that reading is variable among several individuals according to their experiences; the reader digests his lecture. The hypotheses which suggests this fact were that the individual's social and cultural context would act as a conditioning factor of variety of interpretations and that the elements of which social classes would extract inferences according to his social and cultural background. It was used an established pause technique previously marked in the text in students belonging to the different social classes from particular or public schools. Pre-test and test were applied in students of 5th or 7th level of the 1st degree, and it was verified that from the comparative study of the results, there is influence of previous experiences of the reader in the comprehension of texts and there is yet the influence from social and cultural context, during the inferencial process. As a conclusion, one can say that from the comparative analysis of cases that the diversity of comprehension about only one text it is due to the reader's world knowledge. Each one has his own understanding of the world which is directly related with his social class; students of different social class have different world understandings which determines different readings of the same text.